Physiological regulation for enhancing biosynthesis of biofilm-inhibiting secondary metabolites in Streptomyces cellulosae: Regulation for enhancing biosynthesis of antibiofilm - Mahmood, Kochar Idrees; Najmuldeen, Hastyar Hama Rashid; Rachid, Shwan Kamal (Cellular and Molecular Biology, 2022)
Although the production of the secondary metabolite is frequently restricted, methods to regulate and optimize their synthesis are extremely beneficial. The current study proposes to enhance the production of antibiofilm metabolite in Streptomyces cellulosae (S. cellulosae). It was isolated from soil by growing on Gause's media and identified by colony morphology and genomic sequencing of 16S rDNA. Antibacterial and antibiofilm activities of the isolates were screened against a series of pathogenic bacteria by agar plug diffusion and 96 well microtiter plate methods, respectively. Physiological regulation of the bacterial bioactivity against biofilm formation was monitored under different cultural conditions. The isolated Streptomyces sequence analysis of the 16S rDNA was 100% identical to the sequence of S. cellulosae strain NBRC 13027. Physical (temperature and pH) and chemical (carbon, nitrogen, and minerals) culture medium factors have shown variable impacts on the growth and bioactive substances of S. cellulosae. Moreover, results of simple linear regression and correlation suggested that most of the physiological regulations with the highest response (r2= 0.85-0.99; p<0.01) and linearly (r= 0.88-0.99; p<0.01) were correlated between microbial biomass and crude extract. Lastly, under different culture growth conditions, biofilm inhibition was tested against Pseudomonas aeruginosa (P. aeruginosa). The physiological regulation results exhibited that 1 μg/mL of the extract was the most efficient concentration against biofilm formation in P. aeruginosa while 3 μg/mL is an effective bactericidal dose against P. aeruginosa. We concluded that S. cellulosae can produce antibacterial and antibiofilm metabolites. Physiological regulation is considered a powerful tool that can be used for increasing the biosynthesis of the active metabolites and biomass.